Computer aided diagnostic system for lung diseases - Mohd. Noor, Norliza; Sheikh Salleh, Sheikh Hussain; Syed Abu Bakar, Syed Abdul Rahman; Mahmod, Nooraznim (Centre for Islamic Studies and Social Development, 2006)
Report published by the World Health Organization (WHO) in 2006 stated that tuberculosis kills nearly two million people per year (5000 people per day) and about one third of the worlds population is infected with TB world wide. In 2000 alone, tuberculosis accounts for 2.5% of the global burden of disease and is the most common cause of death in young women, killing more women than all causes of maternal mortality combined. The second lung disease that is equally worth investigating is lung cancer. Lung cancer is the leading killer cancer among its group, contributing to 17.8 percent of all total cancer deaths, as reported by WHO in 2006. The research project concentrates on the development of computer aided diagnostics system for detection and monitoring lung disease namely pulmonary tuberculosis (PTB). The system will aid the medical practitioner greatly especially in the visual interpretation of the chest radiograph. The system provides an objective technique that is more efficient, consistent and accurate in the detection of PTB and lung cancer (LC). It is also able to discriminate between normal lung and lung that is infected with PTB or lung cancer. For managing the patient data more efficiently, an electronic database system for PTB and lung cancer patients was developed in this research project. The data was provided by the Institute of Respiratory Medicine (IPR), Kuala Lumpur Hospital. The data was screened by their medical consultant where 3 categories was selected that are PTB confirmed cases, lung cancer confirmed cases and PTB + other disease/s. There are three end products of this project that are; 1. Computer Aided Diagnostics for Detecting PTB/LC (CAD-D-PTB/LC) - This system is able to discriminate PTB, LC and normal lung with 85% success rate. 2. Computer Aided Diagnostics for Monitoring PTB (CAD-M-PTB) - This system is used for monitoring objectively the patients progress while receiving treatment. 3. Electronic PTB and LC patients database system. - This system emulates Institute of Respiratory Medicine patient file system. The system comes complete with digital chest radiograph and bronchoscopy image viewing facility.